EVALUASI PENERAPAN SISTEM INFORMASI MANAJEMEN PUSKESMAS (SIMPUS) DENGAN METODE HOT-FIT DI PUSKESMAS GATAK - Cahyani, Anggita Pramesti Putri; Hakam, Fahmi; Nurbaya, Fiqi (Program Studi D3 Rekam Medis dan Informasi Kesehatan, 2020)
Information system evaluation is the process of knowing the extent of the information system.From a preliminary study of researchers in the health center gatak about the number of humanresources has been found that the lack of human resources is competent in the it field, not all officersunderstand the use of the Health Center Management Information System (HCMIS), sometimes anerror server causes a breakdown in service processes. The purpose of this study is to evaluate theapplication of Health Center Management Information System in the health center gatak and knowthe use of quality services indicator Health Center Management Information System by explainingthe compatible systems component that is human, technology and organization. This type of researchis a descriptive analytic study with a qualitative approach. Research subject exist six is the head ofmedical records, one operator polyclinic, Hcmis coordinator, one Hcmis operator, head of themedical center, and one pharmacist. The sample retrieval technique used is purposive sampling. Theresults of this study, is known to what extent the Health Center Management Information Systemprogram is running, to provide input for an evaluation at health center gatak for the front becausehuman, technology, and organization compatibility really does affect information systems. It ishoped that there will be periodic training so that the implementation of Health Center ManagementInformation System use becomes easier.